Efficiency evaluation in public road transport: a stochastic frontier analysis - Jarboui, Sami; Forget, Pascal; Boujelben, Younes (Transport, 2015)
This paper measures the technical efficiency of 54 public road transport operators and investigates the degree to which various factors influence efficiency levels in these firms. The study makes an attempt to provide an overview of the general status of different operators in 18 countries. Stochastic Frontier Analysis (SFA) methods are applied to our sample over a twelve year period from 2000 to 2011. To our knowledge, this is the first comprehensive analysis of technical efficiency of public road transport operators in 18 countries using parametric method. Our empirical results indicate that investment, operating profit and firm size have a significant influence on technical efficiency levels. We find that technical efficiency level of public road transport operators varies between 0.458 and 0.95. We also observe that large-size operators with more investment capacity tend to be more technically efficient than small-size operators. Finally, we find that operators from developed countries are technically more efficient than those of developing countries.First published online: 23 May 2013